2016
DOI: 10.1111/crj.12519
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis and systematic review of procalcitonin‐guided treatment in acute exacerbation of chronic obstructive pulmonary disease

Abstract: Introduction: To evaluate the method of procalcitonin (PCT)-guided treatment on antibiotics in acute exacerbation of chronic obstructive pulmonary disease (AECOPD).Methods: Database including PubMed, EMBASE, and the Cochrane Central Register of Controlled Trails were searched to find relevant trails. Randomized and quasirandomized trials of PCT-guided treatment in adult patients with AECOPD were included. Effects on primary outcome (i.e., antibiotic prescriptions, mortality, and clinical success) were accessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Yet, a post hoc analysis of a randomized, placebo-controlled trial that failed to show a positive effect of antibiotics in COPD exacerbations suggested that patients with low PCT concentrations during a COPD exacerbation might also benefit from antibiotic treatment 29. Above all, the results from a meta-analysis suggest that PCT-guided treatment can safely reduce antibiotic overuse in patients with AECOPD,30 but the cutoff of PCT to use antibiotics has no consensus; further studies are needed to evaluate the utility of PCT measurement 31…”
Section: Methodsmentioning
confidence: 99%
“…Yet, a post hoc analysis of a randomized, placebo-controlled trial that failed to show a positive effect of antibiotics in COPD exacerbations suggested that patients with low PCT concentrations during a COPD exacerbation might also benefit from antibiotic treatment 29. Above all, the results from a meta-analysis suggest that PCT-guided treatment can safely reduce antibiotic overuse in patients with AECOPD,30 but the cutoff of PCT to use antibiotics has no consensus; further studies are needed to evaluate the utility of PCT measurement 31…”
Section: Methodsmentioning
confidence: 99%
“…Serum PCT has been suggested as a promising, rapid, and objective test to confirm or exclude bacterial infection and to help guide doctors prescribe or withhold antibiotics. Meta-analyses have shown that PCT-guided treatment can safely reduce antibiotic overuse in patients with acute exacerbations of chronic obstructive pulmonary disease (COPD) (Lin and Pang, 2016) and those with respiratory tract infections (Schuetz et al, 2012). To the best of our knowledge, this is the first meta-analysis to address the use of PCTguided antibiotic therapy in subjects with asthma exacerbation.…”
Section: Discussionmentioning
confidence: 98%
“…Procalcitonin is another biomarker that can be used to differentiate active bacterial infection from viral infection or chronic bacterial colonization. Recent meta-analyses indicate that procalcitoninguided treatment can safely reduce antibiotic overuse in patients with acute exacerbations of COPD [42,43]. Accordingly, we should consider using this approach to select those patients most likely to benefit from antibiotics.…”
Section: Discussionmentioning
confidence: 99%